Enhancement of Dynamic Damping Eco-Friendly Railway Concrete Sleepers using Crumb Rubber - Ruslim, Abdul Aziz (IRC, 2019)
The use of crumb rubber in the concrete is a good alternative for reducing rubber waste that massively come from waste tyre. It is also can improve environment when waste tyre can be recycled into genuine used. In this study, dynamic properties of high-strength rubberized concrete have been investigated to maintain the compressive strength, flexural strength, tensile strength and damping characteristics by replacing fine aggregates as crumb rubber. 13 mix sample have been determined by RMS software will be carried out. The result confirms that by adding crumb rubber into concrete can reduced the compressive strength of the concrete. So, the addition of nano silica will be maintain the strength of the concrete while increasing the damping of the concrete. It is therefore recommended to consider using rubberized concrete in designing railway sleepers as this will improve characteristics of the sleepers while reducing waste to environment